1993
DOI: 10.1007/bf02231527
|View full text |Cite
|
Sign up to set email alerts
|

Increased soluble IL-2 receptor in serum of patients with systemic lupus erythematosus

Abstract: We estimated the concentration of soluble IL-2R (sIL-2R) in the serum of patients with systemic lupus erythematosus (SLE) and examined the relationship between the serum levels of sIL-2R and clinical features or laboratory data. We found that elevated levels of sIL-2R were present in the serum of SLE patients with discoid rash, and sIL-2R concentrations were correlated with the soluble CD4 and soluble CD8 concentrations but not with classical serological marker, anti-DNA antibody or complement titer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Recent studies have identified several cytokines that play important roles in the immunopathogenesis of various immune disorders, such as SLE [19][20][21]. Other compounds, such as soluble interleukin-2 (IL-2) receptor, soluble CD4 and soluble CD8, have also been examined and are considered to play important roles in the aberrant immune function encountered in SLE [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified several cytokines that play important roles in the immunopathogenesis of various immune disorders, such as SLE [19][20][21]. Other compounds, such as soluble interleukin-2 (IL-2) receptor, soluble CD4 and soluble CD8, have also been examined and are considered to play important roles in the aberrant immune function encountered in SLE [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…77 SIL-2R expression is also increased in the peripheral blood of SLE patients, especially in those experiencing discoid skin lesions. 80 It is unclear from these studies what role either the soluble or surface IL-2Rs may be playing in the wound healing problems found in SLE patients. Thus, more study of the actions of downstream IL-2R signaling and the behavior of the IL-2R are required in this context.…”
Section: Il-2 In Diseases Involving Wound Healingmentioning
confidence: 99%